Alcohol‐related dysmorphic features as predictors of neurodevelopmental delay in infants and preschool‐aged children: Results from a birth cohort in Ukraine. (14th November 2022) - Bandoli, Gretchen; Coles, Claire; Kable, Julie; Jones, Kenneth Lyons; Delker, Erin; Wertelecki, Wladimir; Yevtushok, Lyubov; Zymak‐Zakutnya, Natalya; Granovska, Iryna; Plotka, Larysa; Chambers, Christina; ,
Abstract: Background: Cardinal and non‐cardinal dysmorphic features are associated with prenatal alcohol exposure (PAE); however, their association with neurodevelopment is less clear. The objective of this study was to determine whether alcohol‐related dysmorphic features predict neurodevelopmental delay in infants and toddlers. Methods: We analyzed a prospective pregnancy cohort in western Ukraine enrolled between 2008 and 2014. A dysmorphology examination comprising body size and three cardinal and 14 non‐cardinal dysmorphic features was performed at approximately 6 to 12 months of age. PAE was self‐reported and operationalized as absolute ounces of alcohol per day around the time of conception. Neurodevelopment was assessed at 6 to 12 months with the Bayley Scales of Infant Development‐II (BSID‐II), and at 3.5 to 4.5 years of age with the Differential Ability Scales‐II, the Child Behavior Checklist, and multiple measures that were used to create an executive functioning factor score. We performed logistic regression to predict children's neurodevelopment from dysmorphic features, growth measures, sex, and PAE. Results: From an analytic sample of 582 unique children, 566 had BSID‐II scores in infancy, and 289 completed the preschool battery. Models with all cardinal and non‐cardinal dysmorphic features, growth measures, sex, and PAE performed better than models with subsets of those inputs. In general, models had poor performance classifying delays in infancy (area under the curve (AUC) <0.7) and acceptable performance on preschool‐aged outcomes (AUC 0.75). When the sample was limited to children with moderate‐to‐high PAE, predictive ability improved on preschool‐aged outcomes (AUC 0.76 to 0.89). Sensitivity was relatively low for all models (12% to 63%), although other metrics of performance were higher. Conclusion: Predictive analysis based on dysmorphic features and measures of growth performed modestly in this sample. As these features are more reliably measured than neurodevelopment at an earlier age, the inclusion of dysmorphic features and measures of growth in predictive models should be further explored and validated in different settings and populations. Abstract : The objective was to determine whether alcohol‐related dysmorphic features predicted neurodevelopmental delay in infants and toddlers in a birth cohort in Ukraine. Models with all cardinal and non‐cardinal dysmorphic features, growth measures, sex and prenatal alcohol exposure had the best performance, although sensitivity was relatively low.